Old immigrants and their choice of place of residence - Čabrilo Blagojević, Ljiljana (National Interest, 2022)
The modern world has long faced two types of demographic changes: intense population migration and ageing. Migration flows evolve and change, influenced by globalization and better transport and communication possibilities. Temporary immigration gradually becames permanent. Over time, immigrants also get old and increase the already significant number of elderly people in the host country. Once retired, the question arises as to the choice of their place of residence: to stay in the host country, or to return to the country of origin?